Comparisons of the densification, microstructure and mechanical properties of boron carbide sintered by hot pressing and spark plasma sintering. Issue 2 (1st February 2018) - Zhang, Xiaorong; Zhang, Zhixiao; Wen, Ruolin; Wang, Guangshuo; Zhang, Xiaoliang; Mu, Jingbo; Che, Hongwei; Wang, Weimin
Abstract: Sintering experiments on boron carbide (B4 C) are performed by hot pressing (HP) and spark plasma sintering (SPS). Results show that the maximum densification rate of SPS occurs at approximately 1850 °C, which is earlier than that of HP. The microstructure of samples sintered by HP is very homogeneous and has a relative density of about 91%. In SPS, a high relative density of >94% can be realised, but the microstructure of the samples presents two obviously different regions. The microstructure of region I is very similar to those of samples sintered by HP. However, region II, which has a non-uniform grain size distribution, shows considerably higher relative density than region I. The mechanical properties of the samples sintered by SPS are superior to those of the samples sintered by HP because of the formation of region II.